BIOAUGMENTATION OF MICROORGANISMS ON THE DECOMPOSITION OF A MIXTURE OF DAIRY CATTLE MANURE AND CHICKEN EXCRETA AS SOLID ORGANIC FERTILIZER - Riyanto, Kirana Fairuza; Ridwan, Roni; Harlia, Ellin (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
Solid organic fertilizer efficiently utilizes livestock waste, with laying hen excreta providing the highest nitrogen (N) content among livestock manure. Combining laying hen excreta with dairy cow manure and fiber sources as a fertilizer base is expected to meet KEPMENTAN No. 261 of 2019 standards. To maintain essential nutrients (N, P, K), the fertilizer is enriched with Pseudomonas sp., Herbasirillum sp., and Streptomyces sp. This study aims to analyzing the effect of chicken excreta on macronutrient content (N, P, K), carbon (C) levels, C/N ratio, coliform presence, and microbial viability. The experiment followed a completely randomized design (CRD) with six treatments, namely P1: (95% Combination of DCF and FS + 5% Laying Hen Excreta), P2: (90% Combination of DCF and FS + 10% Laying Hen Excreta), P3: (85% Combination of DCF and FS +15% Laying Hen Excreta), MP1: (95% Combination of DCF and FS + 5% Laying Hen Excreta + 10% MK), MP2: (90% Combination of DCF and FS + 10% Laying Hen Excreta + 10% MK) and MP3: (85% Combination of DCF and FS + 15% Laying Hen Excreta + 10% MK). DCF (Dairy Cow Feces), FS (Fibre Source), MC (Microbial Consortium), SOF  (Solid Organic Fertilizer). Results showed that adding 15% laying hen excreta enriched with bacteria significantly increasing (P≤0.05) macronutrient content, viability, C/N ratio, and coliform presence but did not significantly affect carbon (C) content.